Potensi ekonomi sirkular dalam pengembangan klaster industri daur ulang kapal di indonesia - Sunaryo Sunaryo; Aufa Rahma Asyifa; Wanginingastuti Mutmainnah; Hariyanto (BKS-TM Indonesia, 2025)
The objective of the research is to investigate the potential of circular economics in the development of the national ship recycling industry cluster. In conjunction with the entry into force on 26 June 2025 of the Hong Kong International Convention for the safe and environmentally sound recycling of ships, which establishes mandatory regulations to govern the way ships are recycled, modern ship recycling facilities are also growing in Indonesia. This growth is mainly due to the constant increase of uneconomical and old national shipping fleet. Which needs to be renewed and sent to the ship recycling facilities, due to the impact of the Cabotage principle, and due to high demand for raw materials from the iron and steel industry. in modern ship recycling activities, which comply with the regulations of the Hong Kong Convention, the